Multimodal poetics in digital literature: a corpus-based analysis of visual-verbal design, screen-based textuality, and reader interaction - Ridhatullah Assyabani (Asosiasi Relawan dan Pengelola Jurnal LPTNU (ARJUNU), 2025)
Background: Digital literature has transformed literary experience by shifting reading from a page-bound encounter with verbal text into a screen-based engagement with visual design, textual movement, interface structure, and reader participation. Objective: This study aims to examine how selected digital-born literary works construct meaning through the integrated operation of verbal, visual, and interactive forms. Method: Using a qualitative interpretive design, the study analyses works drawn from recognized electronic literature archives through Multimodal Discourse Analysis, Digital Poetics Analysis, and Interface and Interaction Analysis. Results: The findings show that visual-verbal configuration functions as a core poetic mechanism, in which typography, layout, image, colour, spatial arrangement, and screen composition actively reshape verbal meaning. The study also finds that fragmentation, movement, and screen-based textuality expand poetic form beyond stable printed structures by making language dynamic, procedural, and temporally organized. Implication: Reader navigation further emerges as a crucial mode of meaning-making, as clicking, scrolling, selecting, waiting, observing, and activating textual elements transform reading into a performative negotiation between agency and constraint. Novelty: The novelty of this study lies in its corpus-based multimodal poetics framework, which integrates visual-verbal design, digital textual dynamics, and interactive readerly performance into a single analytical model for examining digital-born literature.